2021
DOI: 10.1021/acs.iecr.1c03074
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Assessment of the Endothelial Glycocalyx To Address Cardiovascular Disease

Abstract: Endothelial cell (EC) glycocalyx (GCX) loss permits blood circulating particle infiltration of the vessel walls and leads to vascular dysfunction, atherosclerosis, and serious downstream cardiovascular events, motivating EC GCX regeneration to treat cardiovascular disease. This review discusses the benefits and drawbacks of current options for EC GCX regeneration and assessment. Existing pharmaceutical therapies are being explored for their applicability to EC GCX regeneration, while nutraceuticals are under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 138 publications
1
20
0
Order By: Relevance
“…ALM fluid therapy appears to support a high-flow, hypotensive, vasodilatory state with maintained endothelial-glycocalyx patency and mitochondrial function ( Granfeldt et al, 2015 ; Letson et al, 2020 ). In addition, Dubick and colleagues from the US Army Institute of Surgical Research independently reported that ALM therapy nearly completely reversed endothelial glycocalyx damage after severe hemorrhagic shock ( Torres Filho et al, 2017 ; Banerjee et al, 2021 ), which is consistent with our findings of rapid 5 min correction of coagulopathy following different traumatic injuries ( Letson et al, 2012 ; Letson and Dobson, 2015 ; Letson and Dobson, 2018 ; Dobson et al, 2022b ; Letson et al, 2022 ). A curious result of ALM therapy is that it confers multi-protection against: 1) sterile injury ( Dobson and Letson, 2016 ; Dobson and Letson, 2020 ; Dobson et al, 2021b ), 2) infection ( Griffin et al, 2014 ; Griffin et al, 2016 ) and 3) lipopolysaccharide (LPS)-induced endotoxemia ( Granfeldt et al, 2013 ), which implies a common mechanism of action to blunt DAMPs, PAMPs and other inflammatory signals.…”
Section: The Path Forward: Towards An Adenosine Lidocaine and Magnesi...supporting
confidence: 91%
See 2 more Smart Citations
“…ALM fluid therapy appears to support a high-flow, hypotensive, vasodilatory state with maintained endothelial-glycocalyx patency and mitochondrial function ( Granfeldt et al, 2015 ; Letson et al, 2020 ). In addition, Dubick and colleagues from the US Army Institute of Surgical Research independently reported that ALM therapy nearly completely reversed endothelial glycocalyx damage after severe hemorrhagic shock ( Torres Filho et al, 2017 ; Banerjee et al, 2021 ), which is consistent with our findings of rapid 5 min correction of coagulopathy following different traumatic injuries ( Letson et al, 2012 ; Letson and Dobson, 2015 ; Letson and Dobson, 2018 ; Dobson et al, 2022b ; Letson et al, 2022 ). A curious result of ALM therapy is that it confers multi-protection against: 1) sterile injury ( Dobson and Letson, 2016 ; Dobson and Letson, 2020 ; Dobson et al, 2021b ), 2) infection ( Griffin et al, 2014 ; Griffin et al, 2016 ) and 3) lipopolysaccharide (LPS)-induced endotoxemia ( Granfeldt et al, 2013 ), which implies a common mechanism of action to blunt DAMPs, PAMPs and other inflammatory signals.…”
Section: The Path Forward: Towards An Adenosine Lidocaine and Magnesi...supporting
confidence: 91%
“…Disruption to the BBB is important because the brain loses its ‘immune privilege’ over the rest of the body ( Figure 2 ). However, if tissue perfusion is restored early, the glycocalyx has a remarkable capacity to repair itself and restore its barrier functions ( Zeng and Tarbell, 2014 ; Banerjee et al, 2021 ; Jin et al, 2021 ). Timing of repair appears to depend upon the duration and extent of hypoperfusion, and the type and severity of trauma.…”
Section: Second Pillar: the Endothelial Glycocalyxmentioning
confidence: 99%
See 1 more Smart Citation
“…10,25 Furthermore, there are nutraceutical options like the patent-pending Arterosil, which contains rhamnan sulfate, a HS-mimicking polysaccharide. 42,43 Although Arterosil heals GCX, improves arterial elasticity, and attenuates atherosclerosis, 43,44 like sulodexide, its active component is not found naturally in the body and could trigger inflammation. 42 Additionally, the nutraceutical Endocalyx was recently developed (2018) and is comprised of HA, HS-like fucoidan, and glucosamine for HS and HA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Although Arterosil heals GCX, improves arterial elasticity, and attenuates atherosclerosis, 43,44 like sulodexide, its active component is not found naturally in the body and could trigger inflammation. 42 Additionally, the nutraceutical Endocalyx was recently developed (2018) and is comprised of HA, HS-like fucoidan, and glucosamine for HS and HA synthesis. 45 In a non-peer-reviewed pilot study of the effects of Endocalyx in 13 human subjects, it was shown to stabilize GCX 45,46 ; however, further F I G U R E 1 "Connect the dots."…”
Section: Introductionmentioning
confidence: 99%